Cultural Moduses of Students and Their Influence on the Formation of Life Plans - M. A. Golovchin (Высшее образование в России, 2024)
The purpose of the study is to identify cultural modes that currently most actively influence the spiritual life and worldview of representatives of the younger generation, especially in terms of their formation of plans for the future. Based on the approaches of G. Hofstede and A.A. Auzan to culture proposed a methodology for studying cultural moduses as specific manifestations of life values and practices in the spiritual life of society. In total, the study examines four modes (K, CI, IC, I), which describe various manifestations in the public consciousness of power distance, gender model of decision making, priority of interests, attitude to uncertainty, as well as the short-term mobilization of vital resources. We proposed an algorithm for studying cultural moduses within the framework of sociological research, for testing of which we used a subset of data from the project of the Russian Society of Sociologists “Cultural Heritage and the Connection of Generations” (2022).The study found that modern students have different cultural moduses. The most common are carriers of “intermediate” modus, which brings optimism regarding the interaction of youth culture and social orders (institutions) formed by economic institutions. At the same time, it was revealed that the modes have different effects on the plans of the respondents. In particular, holders of the “IC” modus (who are represented most massively in the sample) after receiving a profession are less likely to remain inclined to live and work in the country.The scientific novelty of the research lies in the development of the author’s approach to the study of the planning process on the part of the younger generation through the analysis of four cultural moduses, as well as its testing. The practical significance of the research results lies in the possibility of their use within the framework of strategic design of youth and educational policies.